THE EFFECT OF PHONE USE ON EARLY CHILDREN’S SOCIAL EMOTIONAL DEVELOPMENT - Nurul Fadilah Hsb; Najwa Kholida; Najwa Rahmi; Maghfiroh Maghfiroh; Masganti Sitorus (Sean Institute, 2023)
This research aims to investigate the influence of early childhood social-emotional development on smartphone usage in RA Darun Najwa, Percut Sei Tuan District, Bandar Khalipah Village, Deli Serdang Regency. The results of observing the use of smartphones by young children include increased emotional withdrawal, diminished creativity, and sleep disturbances. In this study, the author conducted a literature review by collecting and studying existing literature from various sources such as journals, articles, websites, and others related to this research. The findings indicate that the use of smartphones among young children can have negative impacts on their social interaction, communication development, sleep patterns, and mental health. Excessive usage can reduce face-to-face interactions with friends and family, limit social skills, hinder the reading of emotional expressions, reduce engagement in group activities, and potentially lead to social isolation. Inappropriate content accessible through smartphones also has negative effects on children's social-emotional development. Furthermore, excessive smartphone use can disrupt sleep and contribute to mental health issues.